2019
DOI: 10.3389/fncel.2019.00307
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Changes in Microglia Transcriptional Networks Following Traumatic Brain Injury

Abstract: The neuroinflammatory response to traumatic brain injury (TBI) is critical to both neurotoxicity and neuroprotection, and has been proposed as a potentially modifiable driver of secondary injury in animal and human studies. Attempts to broadly target immune activation have been unsuccessful in improving outcomes, in part because the precise cellular and molecular mechanisms driving injury and outcome at acute, subacute, and chronic time points after TBI remain poorly defined. Microglia play a critical role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 99 publications
4
66
1
Order By: Relevance
“…These microglial changes could not only be easily examined with standard histological and immunohistochemical methods but also be used for daily forensic wound age estimation of TBI. A transformation in microglial protein expression towards a more reactive phenotype was also shown in transcriptional studies in rodents after a post-traumatic time course of 2 to 14 days [ 17 ].…”
Section: Discussionmentioning
confidence: 89%
“…These microglial changes could not only be easily examined with standard histological and immunohistochemical methods but also be used for daily forensic wound age estimation of TBI. A transformation in microglial protein expression towards a more reactive phenotype was also shown in transcriptional studies in rodents after a post-traumatic time course of 2 to 14 days [ 17 ].…”
Section: Discussionmentioning
confidence: 89%
“…Microglial and astrocyte activation has been reported at acute and chronic time points post-TBI, as these cells play a pivotal role in the brain’s response to injury [ 34 , 54 , 55 ]. Previous studies have also shown evidence of microglial cell activation in adult humanized Tau mice (hTau) at acute and chronic time points post rCHI [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in an SCI transcriptomic study, a profile of microglia reminiscent of the CD11c+ phenotype was identified (with upregulation of Gpnmb, Spp1, Lpl, Apoe, Igf1, Lgals3, and Itgax among others) and persisted in a full transection model, whereas it contracted concomitantly to recovery in a hemisection model (135), indicative of the transitory nature of this subset. Conversely, in TBI, the microglial signature was further from the CD11c+ microglia signature, although Itgax was among the upregulated genes 14 and 60 days post-injury, possibly indicating once again a dilution of the signature in all microglia (136). In addition, considering the difficulty associated with gating out macrophages from microglia in a context of extensive infiltration, macrophage contamination of the sorted samples cannot be excluded in these studies, potentially complicating interpretation of the observed transcriptomes.…”
Section: Stroke Ischemia and Injurymentioning
confidence: 96%